Монокристаллы YAP:Yb для лазеров ультракоротких импульсов - Ованесян, К. Л.; Дерзян, М. В.; Еганян, А. В.; Кисель, В. Э.; Руденков, А. С.; Кулешов, Н. В.; Петросян, А. Г. (Հայաստանի ԳԱԱ)
Single crystals of yttrium orthoaluminate activated with Yb3+ ions (YAlO3:Yb) are of high interest for diode pumped high-power ultra short pulse lasers emitting in the spectral range around 1 μm. The major parameters of lasers achieved so far can be improved by optimizing the activator concentration and improvement of the structural and optical quality of crystals. One of the problems is occurrence of color centers giving rise to absorption bands in the visible range with tails extending to the near IR. In the present work single crystals of YAlO3:Yb were grown by the Bridgman and Czochralski methods. It is found that under the applied growth conditions absorption associated with color centers in the visible range is much lower in YAlO3:Yb crystals grown by the Bridgman method. The differences in optical quality are attributed to the growth atmosphere (Ar/H2for Bridgman and Ar in the case of Czochralski), and to crystal cooling conditions. The influence of gamma-ray irradiation and thermal annealing on optical absorption inYAlO3:Yb grown by the two methods is studied. The lifetime of Yb3+ is measured in crystals grown by the two methods.
Keywords: Physics